The Research Progress of Electrical Impedance Tomography for Lung Monitoring - Shi, Yan; Yang, ZhiGuo; Xie, Fei; Ren, Shuai; Xu, ShaoFeng (Frontiers in Bioengineering and Biotechnology, 2021)
Medical imaging can intuitively show people the internal structure and morphology information and organ functions of the organism through modern visualization technology, and it is one of the most important inspection methods in clinical medical diagnosis. The currently used medical imaging methods can only be applied to some diagnostic occasions after qualitative lesions have been generated, and the general imaging technology is usually accompanied by radiation and other conditions, while electrical impedance tomography is non-invasive, non-radiation, and functional imaging. EIT is also widely used in the early diagnosis and treatment of some diseases because of these advantages. At present, technologies related to EIT have developed more mature, some image reconstruction algorithms have been used to improve imaging resolution, the development of hardware technology has gradually matured, and the accuracy of data collection and processing has been continuously improved. In terms of clinical application, EIT has also been used for pathological treatment of lungs, brain, bladder, etc. In the future, EIT has a good application prospect in the medical field, which can meet the needs of real-time, long-term monitoring and early diagnosis. Aiming at the application of EIT in the treatment of lung pathology, this article reviews the research progress of electrical impedance tomography, image reconstruction algorithms, hardware system design, and clinical applications used in the treatment of lung diseases. Through the research and introduction of several core components of EIT technology, it clarifies the characteristics of EIT system complexity and its solutions, provides research ideas for subsequent research, and once again verifies the broad development prospects of EIT technology in the future.